2019
DOI: 10.1038/s41467-019-12667-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular features of the UNC-45 chaperone critical for binding and folding muscle myosin

Abstract: Myosin is a motor protein that is essential for a variety of processes ranging from intracellular transport to muscle contraction. Folding and assembly of myosin relies on a specific chaperone, UNC-45. To address its substrate-targeting mechanism, we reconstitute the interplay between Caenorhabditis elegans UNC-45 and muscle myosin MHC-B in insect cells. In addition to providing a cellular chaperone assay, the established system enabled us to produce large amounts of functional muscle myosin, as evidenced by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 72 publications
5
43
0
Order By: Relevance
“…We further replicated these findings using Sf 9 cells engineered to stably express only mouse UNC45A, or UNC45B, demonstrating that endogenous insect HSP90 orthologs were sufficient to function with UNC45. Our findings confirm a recent report where overexpression of the C. elegans UNC45 ortholog was sufficient to fold muscle myosin (MHC-B) in Sf 9 cells without the overexpression of HSP90 ( 55 ). The Sf 9–UNC45 cell lines developed here facilitate the expression of recombinant MYO15 and may prove helpful for other proteins and myosin motors that require UNC45 paralogs to fold and mature correctly.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We further replicated these findings using Sf 9 cells engineered to stably express only mouse UNC45A, or UNC45B, demonstrating that endogenous insect HSP90 orthologs were sufficient to function with UNC45. Our findings confirm a recent report where overexpression of the C. elegans UNC45 ortholog was sufficient to fold muscle myosin (MHC-B) in Sf 9 cells without the overexpression of HSP90 ( 55 ). The Sf 9–UNC45 cell lines developed here facilitate the expression of recombinant MYO15 and may prove helpful for other proteins and myosin motors that require UNC45 paralogs to fold and mature correctly.…”
Section: Discussionsupporting
confidence: 92%
“…MYO3A, MYO6, and MYO7A have all been successfully purified from Sf 9 cells without the use of UNC45 coexpression, suggesting that this chaperone is not a prerequisite for folding ( 63 , 64 , 65 , 66 ). It is interesting to note that the UNC45 family chaperones also target the unfolded myosin motor domain in vitro ( 34 , 55 , 67 ) and potentially do so in response to tissue trauma in vivo ( 68 ). An exciting hypothesis is that UNC45 paralogs may maintain hair cell proteostasis and refold myosin motors in stereocilia as they are denatured and damaged.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, one of the first identified C. elegans ts mutations in UNC45, which affects worm motility and sarcomere organization, is a point mutation in the corresponding codon resulting in E781K substitution (52). It has been recently found that that the worm UNC45 E781K mutant protein has different unfolding Tm as measured by CD, compared to other UCS ts mutants (20), suggesting that this mutation affects the structure of the UCS domain The Y750W (hs Y737W) mutation itself doesn't drastically affect chaperoning ability of UNC45 as shown in rescue experiments with worms (17) and myosin motor domain folding assay in insect cells (20). Our data show that the double mutant 2xW (Y737W, N745W) significantly affects the in vitro chaperoning function of UNC-45 ( Figs.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo mutagenesis analysis revealed that in contrast to a Y750W mutant, which is still capable to restore muscle function, a N758Y mutant failed to rescue a temperature-sensitive unc-45 mutant (in worms carrying the ts allele unc-45(m94, mutation E781K) grown at the nonpermissive temperature. Further analysis of C. elegans mutations affecting myosin-binding groove by the same group confirmed that UNC-45 carrying Y750W mutation was able to support production of soluble myosin motor domain when coexpressed in insect cells, even though to less extent than wt UNC-45 (20). N758Y unfortunately failed to express in insect cells efficiently, suggesting structure destabilizing nature of this mutation.…”
Section: Introductionmentioning
confidence: 95%
“…Structurally, the myosin-interacting element shared by UCS proteins consists of nine copies of the armadillo domain (3,8,(16)(17)(18)(19)(20). Although no human UNC-45 structure is available, homology models have been created via in silico molecular modeling and simulations (21).…”
Section: Introductionmentioning
confidence: 99%